Pengetahuan Tentang Program Merdeka Belajar Kampus Merdeka dan Minat Mengikuti Program Merdeka Belajar Kampus Merdeka Studi Empirik Terhadap Mahasiswa Fakultas Ilmu Pengetahuan Budaya, Universitas Al Azhar Indonesia - Zaqiatul Mardiah; Lusi Lian Piantari (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2022)
The MBKM program was first launched in early 2020 to provide opportunities for students to be active outside the campus. I took part in this program. A number of socialization activities were carried out to provide knowledge about what and how the MBKM program was. In two years, 235 UAI students have participated in 8 MBKM programs. This number can increase as the number of students who know and understand the program increases, as well as their knowledge of the benefits and risks of the program they are interested in. By utilizing Prospect Theory (Tversky and Kahneman, 1992), this study examines the relationship between the knowledge that students have about the MBKM program, both its benefits and risks, their degree of interest in the program, and the choice of the type of program they are interested in. The results indicate that students who have a higher perception of the potential benefits that can be achieved from MBKM activities are expected to have a higher interest in participating in, and recommending the MBKM program to their colleagues with the same risk perception; and vice versa.Keywords – By utilizing the Prospect Theory of Tversky and Kahneman, 1992, By utilizing the Prospect Theory of Tversky and Kahneman, 1992 Benefits, knowledge, prospects, risks, theory